2017
DOI: 10.1111/1346-8138.13933
|View full text |Cite
|
Sign up to set email alerts
|

Management of alopecia areata: Updates and algorithmic approach

Abstract: Alopecia areata is a chronic, recurrent and non-scarring alopecia. The prognoses of patients are very diverse. The larger the area of hair loss, the poorer the treatment response and greater the probability of chronic disease progression. Numerous treatments have been introduced, but curative treatments have yet to be established. The long-term efficacy of the current treatments is minimal, and the therapeutic response varies widely. Recent clinical trials have attempted to apply therapeutic metrics, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 131 publications
(220 reference statements)
2
67
0
2
Order By: Relevance
“…1 The prevalence is 0.1-0.2% with the lifetime risk of 2%. 2 As AA is considered a T cell-mediated autoimmune disorder, several studies have shown that patients with AA are more likely to develop other autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, type I diabetes mellitus and vitiligo compared to the normal population. [3][4][5] Vitamin D is a group of fat-soluble secosteroids, synthesized in epidermal keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence is 0.1-0.2% with the lifetime risk of 2%. 2 As AA is considered a T cell-mediated autoimmune disorder, several studies have shown that patients with AA are more likely to develop other autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, type I diabetes mellitus and vitiligo compared to the normal population. [3][4][5] Vitamin D is a group of fat-soluble secosteroids, synthesized in epidermal keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…One retrospective case series of MTX was included that suggested useful regrowth in around 50% of patients. Lee and Lee searched PubMed until March 2017 and rated the evidence using the United States Preventive Service Task Force recommendation . MTX was listed as a third‐line therapy based on three observational studies, with a rating of ‘fair’ for quality of evidence, mid‐range for quantity of evidence and low for benefit‐to‐risk ratio.…”
Section: Critical Appraisal Of the Evidencementioning
confidence: 99%
“…Application of the evidence to our patient with alopecia totalis is challenging given that many patients included in the studies had AA for < 1 year, less severe disease at baseline and were treated with other forms of corticosteroid therapy. Corticosteroid monotherapy has also shown similar results; a systematic review reported complete regrowth in 43% overall; however, side‐effects are common and it is advised to avoid longer‐term use where possible . Better case series of MTX monotherapy with consecutive patients are needed to provide a clearer proof of principle before embarking on full‐scale randomized controlled trials that assess MTX alone vs. placebo, or in combination with corticosteroids vs. placebo.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations